The Pivotal Role of Mid-level Implementation Bodies in Italy’s Cohesion Policy - Anna Rita Ceddia (Revue Internationale de Politique de Développement)
This chapter examines the changing dynamics of expenditure management in Italy by connecting them to recent institutional reforms and to their implications for implementation practices. To this end, it maps the actors involved in the programme implementation of the European Social Fund (ESF) and the features related to the reprogramming of the Operational Programme, while analysing their role during the period 2014‒20. Adopting a multilevel perspective, it focuses on the role of mid-level implementation bodies. It highlights the implications of the COVID-19 emergency on implementation and reprogramming activities as well as the and on the interplay between actors. By analysing documents, and by building on empirical observations collected through interviews, the author shows how social practices and modalities of communication are relevant aspects of the policy implementation process, thereby providing a wider picture with regard to fund deployment.